EFEKTIFITAS MEDIA KOMPUTER DENGAN PERANGKAT LUNAK POWERPOINT DALAM MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS MATERI PRONOUN PADA PESERTA DIDIK KELAS X TEKNIK SURVEYING DI SMK NEGERI 3 GORONTALO TAHUN PELAJARAN 2018/2019 - Yusuf, Maryam (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The objective of this research is to enlarge the teaching and learning tools which is basedon PowerPoint software of computer and will be applied to the X grade students of Surveying. Hopefully, by using this media the students can enlarge their learning in English especially in Pronoun. The data of first circle shows that the students who get score less than 75 % is 15 students (40,54 %). Students mastery learning is 75,5 %. Students who are active is 21 students and not active is 16. In the second circle there are 2 students who get score 75 (5,41 %). Students mastery learning is 81,49%. Students who are active is 29 students (78,38%) and 8 students who are not active (21,62%). The data of using media in teaching and learning process shows that all the students are very interesting with the media of PowerPoint software of computer. This is shows that 100 % of the students are exciting, 89,19 % students said that they are easy going to learn, 86,49 % os the students are more active, 75,68 % of the students are motivated to learn, 83,78 % of the students said that they are understand and 0% of students are boring and 89,19 % of students are happy tu study. The student’s motivation in learning material of Pronoun is great, it is about 75,68%. In same case, there are 29 students (78,38%) who said that their English score is betterr. there are 35 students (94,59%) said that they are more motivated in learning. Form those data above can be concluded that teaching and learning process by using PowerPoint software of computer is more significant than the conventional one.